NO-sGC Pathway Modulates Ca2+ Release and Muscle Contraction in Zebrafish Skeletal Muscle - Xiyuan, Zhou; Fink, Rainer H. A.; Mosqueira, Matias (Frontiers in Physiology, 2017)
Vertebrate skeletal muscle contraction and relaxation is a complex process that depends on Ca2+ ions to promote the interaction of actin and myosin. This process can be modulated by nitric oxide (NO), a gas molecule synthesized endogenously by (nitric oxide synthase) NOS isoforms. At nanomolar concentrations NO activates soluble guanylate cyclase (sGC), which in turn activates protein kinase G via conversion of GTP into cyclic GMP. Alternatively, NO post-translationally modifies proteins via S-nitrosylation of the thiol group of cysteine. However, the mechanisms of action of NO on Ca2+ homeostasis during muscle contraction are not fully understood and we hypothesize that NO exerts its effects on Ca2+ homeostasis in skeletal muscles mainly through negative modulation of Ca2+ release and Ca2+ uptake via the NO-sGC-PKG pathway. To address this, we used 5-7 days-post fecundation-larvae of zebrafish, a well-established animal model for physiological and pathophysiological muscle activity. We evaluated the response of muscle contraction and Ca2+ transients in presence of SNAP, a NO-donor or L-NAME, an unspecific NOS blocker in combination with specific blockers of key proteins of Ca2+ homeostasis. We also evaluate the expression of NOS in combination with dihydropteridine receptor, ryanodine receptor and sarco/endoplasmic reticulum Ca2+ ATPase. We concluded that endogenous NO reduced force production through negative modulation of Ca2+ transients via the NO-sGC pathway. This effect could be reversed using an unspecific NOS blocker or sGC blocker.